The handbook of virtue ethics - Hooft, Stan van, 1945-; Athanassoulis, Nafsika, 1973-; Cambridge eBooks (Durham : Acumen Publishing, 2014)
Virtue ethics has emerged as a distinct field within moral theory - whether as an alternative account of right action or as a conception of normativity which departs entirely from the obligatoriness of morality - and has proved itself invaluable to many aspects of contemporary applied ethics. Virtue ethics now flourishes in philosophy, sociology and theology and its applications extend to law, politics and bioethics. The Handbook of Virtue Ethics brings together leading international scholars to provide an overview of the field. Each chapter summarizes and assesses the most important work on a particular topic and sets this work in the context of historical developments. Taking a global approach by embracing a variety of major cultural traditions along with the Western, the Handbook maps the emergence of virtue ethics and provides a framework for future developments.
Introduction / Stan van Hooft -- Part I: Normative Theory. Eudaimonia in contemporary virtue ethics / Anne Baril -- Stoic virtue ethics / Matthew Sharpe -- Naturalistic virtue ethics and the new biology / Richard Hamilton -- Virtue ethics and moral sentimentalism / Michael Slote -- Virtue ethics and utilitarianism / Justin Oakley -- Virtues and rules / Timothy Chappell -- Virtue ethics, virtue theory and moral theology / Glen Pettigrove -- Nietzsche's virtue ethics / Christine Swanton -- Right action and the targets of virtue / Liezl Van Zyl -- Qualified agent and agent-based virtue ethics and the problems of right action / Jason Kawall -- The virtuous person and normativity / Yuval Eylon -- Virtue and identity / Stan van Hooft -- Part II: Types of Virtues. What virtues are there? / Candace Upton -- Intellectual virtues / Heather Battaly -- Virtue, reason and wisdom / Lorraine Code -- Integrity / Damian Cox, Marguerite La Caze and Michael Levine -- The ends of courage / Patrick Shade -- Wit / Raja Halwani and Elliot Layda -- Humility, Kantian style / Jeanine Grenberg -- Love, sex and relationships / Mike W. Martin -- Forgiveness and forgivingness / David McNaughton and Eve Garrard -- The virtue of justice revisited / Mark LeBar -- The virtues of African ethics / Thaddeus Metz -- Classical Confucianism as virtue ethics / Hui-chieh Loy -- Ethics and virtue in classical Indian thinking / Purushottama Bilimoria -- Mindfulness, non-attachment and other Buddhist virtues / Leesa S. Davis -- Virtue in Islam / Recep Alpyagil -- Part III: Applied Ethics. Virtue in the clinic / Matthew McCabe -- Virtue ethics and management / Wim Vandekerckhove -- Virtuous leadership : ethical and effective / Paul Kaak and David Weeks -- Virtue ethics in the military / Peter Olsthoorn -- Sporting virtue and its development / Michael McNamee -- Key virtues of the psychotherapist : a eudaimonic view / Blaine J. Fowers and Emily Winakur -- Part IV: The Psychology of Virtue. Constancy, fidelity and integrity / Clea F. Rees and Jonathan Webber -- Sympathy / Nancy Eisenberg, Tracy L. Spinrad and Zoe E. Taylor -- The problem of character / Christian Miller -- Situationism and character : new directions / Nancy Snow -- Educating for virtue / Nafsika Athanassoulis -- Literature, arts and the education of virtuous emotion / David Carr -- Virtue ethics for skin-bags : an ethics of love for vulnerable creatures / Pedro Alexis Tabensky.
Title from publisher's bibliographic system (viewed on 02 Oct 2015).
Keywords: Virtues -- Handbooks, manuals, etc; Virtue -- Handbooks, manuals, etc; Ethics -- Handbooks, manuals, etc; Electronic books